Quarterly market report for selected legumes, roots, tubers, and other cereals, January to March 2021 - International Food Policy Research Institute (International Food Policy Research Institute, 2021)
This quarterly market report was developed by researchers at IFPRI Malawi with the goal of providing clear and accurate information on the variation of weekly and monthly retail prices of selected agricultural commodities that are important for food security and nutrition in Malawi. The reports are intended as a resource for those interested in agricultural markets in Malawi.